The practice of liberal pluralism - Galston, William A. (William Arthur), 1946- (Cambridge, 2005)
"The Practice of Liberal Pluralism defends the theory of liberal pluralism, a theory based on three core concepts - value pluralism, political pluralism, and expressive liberty - and explores the implications of this theory for politics." "Liberal pluralism helps clarify some of the complexities of real-world political action and points toward a distinctive conception of public philosophy and public policy. It leads to a vision of a good society in which political institutions are active in a delimited sphere and in which, within broad limits, families, civil associations, and faith communities may organize and conduct themselves in ways that are not congruent with principles that govern the public sphere." "Written in a nontechnical style, this book will appeal to professionals in philosophy, political science, law, and policymaking."--Jacket